Taking value conflicts seriously: Technological pluralism as an approach to hydrogen governance - Eugen Octav Popa; Anna Melnyk (Energy Strategy Reviews)
We propose technological pluralism as a governance framework for navigating value conflicts arising from technological change within the energy system. The transition to clean hydrogen serves as a case in point as it gives rise to multiple (and complex) value conflicts. Typically, governance frameworks and other strategic approaches are led by the assumption that value conflicts, to the extent that they arise, can and should be solved. We contest this fundamental assumption by drawing on insights from moral and political philosophy. By specifying the descriptive, normative, and prescriptive tenets of a technological pluralist governance process, we set out a framework for driving transitions while taking value conflicts seriously. With clean hydrogen production as a case in point, we illustrate (a) the analysis of socio-technical change through pluralist lenses and (b) the design of pluralist governance strategies for clean hydrogen. We conclude with the suggestion that technological pluralism might be suited not only for the governance of the hydrogen transition but also for taking value conflicts seriously in the current context of decentralization and inclusion promoted by recent EU energy policy frameworks.